Attempt to Practical Use of Lactobacillus plantarum SP 1-3 in Spray Dried Granule Form for Making Good Quality Silage in Thailand - Ohmomo, Sadahiro; Nitisinprasert, Sunee; Kraykaw, Damurussiri; Pholsen, Pinpaporn; Tanomwongwattana, Somjit; Tanaka, Osamu; Suzuki, Tomoyuki; Nishida, Takehiro (Agriculture and Natural Resources, 2007)
For the practical application of spray-dried granule of Lactobacillus plantarum SP 1-3 isolated from a corn silage prepared in Thailand, a low-cost and convenient culture medium formulated from available materials in Thailand was designed for the large scale culture. The best formulation of culture medium was 2% molasses, 0.5% rice bran, 0.2% yeast extract, 0.2% Na-acetate, 0.05% KH2PO4, 0.02% MgSO4 and 0.01% MnSO4. 4H2O and was used for cultivating spray-dried granule strain SP 1-3. This SP 1-3 granule was stable and kept as the living cell count of 108~9 cfu/g in storing at 4°C for 28 days and surely improved the fermentation quality of Napier grass silage. To use this granule for the preparation of practical scale silage, the low-cost and convenient method to increase the cell mass of Lactic acid bacteria (LAB) strain was developed by using a 5-liter plastic bottled drinking water. The culture solution of SP 1-3 obtained by this method was named “PBS-SP”. The fermentation qualities of Pangola grass and Erianthus silages inoculated with PBS-SP were improved effectively. However, the inoculation of LAB strain has no effect on the reduction of living yeast cell in silage and aerobic deterioration of silage by yeast was remained as a problem to be solved.